Durability of concrete with agro-waste: a local approach to sustainability. Issue 2 (7th January 2019) - Chopperla, Siva Teja; Yamuna, Venkateswaran; Bahurudeen, Abdul; Santhanam, Manu; Gopinath, Athira
Abstract : Sugarcane and rice are cultivated in vast tracts of land in the southern part of India. The bagasse and rice husk that are collected during the processing of sugarcane and rice paddies, respectively, possess good calorific values and are used for supplementary energy production. However, the ash generated in the process is dumped in landfills. This paper evaluates the benefits of using these agro-waste ashes (sugarcane bagasse ash (SCBA) and rice husk ash (RHA)) as cement replacement in concrete, through a systematic investigation of strength and durability characteristics of two different strength grades of concrete. The results indicate that the compressive strength of bagasse-ash- and RHA-blended concretes was higher than that of control ordinary Portland cement (OPC) specimens for both grades of concrete. In addition to improved strength, remarkable resistance against water and air and chloride permeability was observed for the blended cement concrete specimens. In the same way, SCBA- and RHA-blended mortar specimens performed better against sulfate attack compared to control OPC specimens. The paper also evaluates the sustainability impact of the concretes produced using SCBA and RHA, and the results from this study clearly show that these materials provide a local approach to the production of sustainable concrete.